Fast curing siloxane encapsulant and preparation method and application thereof

By rapidly curing the thiol-ene click reaction of the silicone encapsulator, ultraviolet light is used to induce rapid lossless packaging of perovskite solar cells, solving the problems of long molding time of existing packaging materials and the generation of organic small molecules, and improving the stability and service life of the device.

CN117659938BActive Publication Date: 2025-03-04HUAZHONG UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311759116.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-20
Publication Date
2025-03-04
Estimated Expiration
2043-12-20

AI Technical Summary

Technical Problem

The packaging materials of existing perovskite solar cells need to be added to the catalyst, curing agent or solvent during the curing process, resulting in a long molding time and accompanied by the production of small organic molecules, which damages the performance of the device.

Method used

The rapid curing silicone encapsulator is used to achieve rapid lossless packaging at room temperature through the thiol-ene click reaction of vinyl siloxane and thiol-siloxane by using ultraviolet photoinitiator.

Benefits of technology

The rapid in-situ non-destructive packaging of perovskite solar cells is realized, avoiding the problems of high-temperature vacuum environment and organic steam, and improving the stability and service life of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117659938B_ABST
    Figure CN117659938B_ABST
Patent Text Reader

Abstract

The present invention provides a fast-curing siloxane encapsulant and a preparation method and application thereof, including, by mass fraction: 10 to 90 parts of vinyl siloxane; 10 to 90 parts of mercaptosiloxane; 0.1 to 1 part of photoinitiator. The present invention first prepares vinyl siloxane and mercaptosiloxane precursor materials, and prepares a polymer encapsulant with good transparency, anti-aging, high and low temperature resistance, low dielectric loss, good bonding performance and no damage to perovskite solar cells by regulating the material ratio of functional siloxane monomers, the material ratio of functional siloxane precursors, spin coating process and photocuring process procedures. Liquid precursor materials avoid the use of solvents, and at the same time, rapid and lossless encapsulation at room temperature is achieved through mercapto-ene click reaction. This encapsulation process can meet the commercial production process of perovskite devices and improve the service life of perovskite solar cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a fast-curing siloxane encapsulant and a preparation method and application thereof, belonging to the technical field of battery encapsulation. Background Art

[0002] Perovskite solar cells have the advantages of strong light absorption, insensitivity to impurities, and long carrier lifetime. They have great potential in improving efficiency and reducing costs, and therefore have attracted widespread attention from researchers around the world. Since the perovskite light-absorbing layer is easy to hydrolyze, easy to decompose at high temperatures, phase change under temperature changes, and photodecomposition under light and oxygen, the stability of perovskite devices is a key problem that needs to be solved urgently for the development of the perovskite photovoltaic industry. (Science, 2023, 379, 399; Sci. Adv., 2021, 7, eabg0633; Joule, 2022, 6, 1032; Adv. Mater., 2019, 31, 1806823; Chem. Soc. Rev., 2022, 51, 7509.).

[0003] At present, the industry generally adopts the packaging method of polyolefin elastomer (POE) plus butyl rubber (PIB). This packaging strategy can effectively block the damage of external water vapor and oxygen to the device and significantly improve the stability of perovskite devices. However, this packaging strategy requires vacuum hot pressing during the packaging process, which undoubtedly increases the manufacturing cost of the device. At the same time, the high temperature vacuum environment is extremely unfavorable to perovskite batteries, which can easily induce lattice distortion of perovskite and affect the efficiency of the device. UV curing is a mild and controllable packaging process, but it has been reported that organic vapors released during UV curing will damage the efficiency of the device. (Energy Environ. Sci., 2022, 15, 13) Therefore, the development of new packaging materials suitable for perovskite batteries is of great significance to improving device performance and promoting the industrialization of perovskite batteries.

[0004] For the encapsulation polymer materials of perovskite solar cells, excellent water and oxygen barrier properties, good electrical insulation, excellent anti-aging and adhesion properties are necessary. Polysiloxane is a bio-inert material with heat resistance, weather resistance, hydrophobicity, electrical insulation, and low internal stress. It is suitable for extreme conditions and outdoor working environments. It is widely used in aerospace, electronics and electrical, light industry and textiles, and medical and health fields. It is an ideal perovskite solar cell encapsulation material. UV curing technology refers to the use of photoinitiators and ultraviolet light irradiation to cross-link liquid monomers or oligomers in a short time to form a three-dimensional solid network. It is an emerging green and environmentally friendly technology with high efficiency, energy saving, environmental protection, and wide adaptability. However, the encapsulation materials commonly used for perovskite encapsulation are mainly encapsulated by photocuring, thermal curing or thermal deposition. The curing process usually requires the addition of different catalysts, curing agents or solvents for auxiliary curing. The molding time is long, and it is accompanied by the production of small organic molecules, which has a great damage to the device performance of perovskite solar cells. For example, the article "Room temperature nondestructive encapsulation via self-crosslinked fluorosilicone polymer enables damp heat-stable sustainable perovskite solar cells" mentions a self-crosslinked fluorosilicone polymer to achieve lossless encapsulation of perovskite solar cells. Although siloxane undergoes alcoholysis and crosslinking under the catalysis of dibutyltin dilaurate to achieve encapsulation, methanol is also generated at the same time, which poses a potential hazard to perovskite solar cells. The article "Enhanced photovoltaic performance and stability of carbon counter electrodebased perovskite solar cells encapsulated by PDMS" uses polysiloxane to encapsulate perovskite solar cells. Its long-term 80°C heat treatment encapsulation process can easily cause serious damage to perovskite. Traditional photocuring technology is also difficult to be further applied to the encapsulation of perovskite solar cells due to the problem of organic vapor. (EnergyEnviron.Sci.,2022,15,13). Summary of the invention

[0005] The present invention provides a fast-curing siloxane encapsulant and a preparation method and application thereof

[0006] Fast curing silicone encapsulant, in parts by mass, comprising:

[0007] 10 to 90 parts of vinyl siloxane;

[0008] 10 to 90 parts of mercaptosiloxane;

[0009] 0.1 to 1 part of photoinitiator.

[0010] The double bond content of the vinyl siloxane is 0.01 to 0.5 mol / 100g.

[0011] The mercapto content of the mercaptosiloxane is 0.01 to 0.4 mol / 100g.

[0012] The preparation method of the fast-curing silicone encapsulant comprises the following specific steps:

[0013] Preparation of Vinyl Siloxane:

[0014] Cyclosiloxane, vinylsiloxane monomer, hexamethyldisiloxane and concentrated hydrochloric acid were mixed at room temperature, refluxed at 30-120°C for 0.5-5h, allowed to stand at room temperature, washed three times with saturated sodium bicarbonate / water / ethanol solution, and distilled at 120°C for 2h in a vacuum environment of -0.1Mpa to obtain a colorless transparent oily liquid.

[0015] Preparation of mercaptosiloxane:

[0016] Cyclosiloxane, mercaptosiloxane monomer, hexamethyldisiloxane and concentrated hydrochloric acid were mixed at room temperature, refluxed at 30-120°C for 0.5-5h, allowed to stand at room temperature, washed three times with saturated sodium bicarbonate / water / ethanol solution, and distilled at 120°C for 2h in a vacuum environment of -0.1Mpa to obtain a colorless transparent oily liquid.

[0017] The cyclosiloxane is one or more than two of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and tetraphenyltetramethylcyclotetrasiloxane.

[0018] The vinyl siloxane monomer is one or more of tetravinylcyclotetrasiloxane and methacryloxypropylmethyldimethoxysilane.

[0019] The fast-curing siloxane encapsulant does not require the addition of solvents during the mixed preparation process. Under ultraviolet conditions, it is rapidly cured through a photo-induced mercapto-ene click reaction, thereby achieving lossless encapsulation of perovskite solar cells.

[0020] The packaging process is as follows:

[0021] The photoinitiator is dissolved in vinyl siloxane, and then mixed evenly with mercaptosiloxane monomer, and the uncured polymer siloxane solution is spin-coated on a clean glass cover plate to prepare a siloxane encapsulation adhesive film with uniform thickness;

[0022] Then, a glass cover with a silicone encapsulation adhesive film is covered on the perovskite solar cell, and ultraviolet light is used to initiate the thiol-ene click cross-linking of double bonds and thiol groups, thereby achieving rapid in-situ lossless encapsulation of the perovskite solar cell.

[0023] The spin coating rate is 3000 rpm, and the spin coating time is 30 s.

[0024] The ultraviolet light is 365nm and the intensity is 50mW / cm 2 , the illumination time is 10 to 60 seconds.

[0025] The packaging material of perovskite solar cells first needs to have water and oxygen barrier properties, and at the same time, to prevent the mechanical stress during the packaging process from damaging the device. Therefore, the present invention controls the distribution of functional groups on the molecular chain to obtain a suitable "aggregation degree", thereby forming a suitable "soft segment" and "hard end" distribution in the three-dimensional network structure of the polysiloxane encapsulation glue, forming a dense and flexible cross-linked structure, and achieving good water and oxygen barrier properties and mechanical strength matching the perovskite solar cell.

[0026] Good water and oxygen barrier and suitable mechanical strength of the encapsulation material are important conditions for achieving perovskite solar cell encapsulation, and the crosslinking density of the polymer is an important factor affecting the material density and mechanical properties. Therefore, the present invention controls the crosslinking density of the polysiloxane encapsulation by controlling the material ratio of each component to obtain a polysiloxane encapsulation adhesive with good water and oxygen barrier and suitable mechanical strength.

[0027] The present invention first prepares vinyl siloxane and mercaptosiloxane precursor materials, and prepares a polymer encapsulation adhesive having good transparency, anti-aging, high and low temperature resistance, low dielectric loss, good bonding performance and no damage to perovskite solar cells by regulating the material ratio of functional siloxane monomers, the material ratio of functional siloxane precursors, spin coating process and light curing process procedures. The liquid precursor material avoids the use of solvents, and at the same time, a mercapto-ene click reaction is used to achieve rapid and lossless encapsulation at room temperature. This encapsulation process can meet the commercial production process of perovskite devices and improve the service life of perovskite solar cells.

[0028] Compared with the existing ethylene-octene copolymer packaging materials, which have the problems of high cost, high processing difficulty, easy hanging of film lips, etc., the siloxane packaging glue used in the present invention has high transparency, low internal stress, high electrical insulation, yellowing resistance, high and low temperature resistance and stress cracking resistance, making it more suitable for lossless packaging of perovskite solar cell devices. At the same time, the packaging material has simple synthesis steps, low cost, and a wide range of raw material sources.

[0029] Compared with the generation of organic vapor in the traditional UV-curing packaging process and the damage to perovskite caused by the vacuum and high-pressure environment in the vacuum hot-pressing packaging process, this siloxane encapsulation adhesive does not require the use of organic solvents, and no small molecule by-products are produced during the packaging process. It can be quickly cured at room temperature through the thiol-ene click reaction. The packaging process is simple and safe, and no packaging equipment is required, which can achieve lossless packaging of perovskite solar cells.

[0030] Compared with the existing siloxane materials in the perovskite field, which have the problems of high packaging temperature, long curing time, and the release of organic small molecules during packaging, the present invention adopts thiol-ene click reaction for photoinitiated polymerization and cross-linking. The reaction conditions are mild, the molding speed is fast, the curing time is short, and no by-products are generated in the reaction, which meets the characteristics of green chemistry. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a photo of a packaged battery of an embodiment;

[0032] Figure 2 FTIR curves of the mercaptosiloxane and its cross-linked polymer products of the embodiments;

[0033] Figure 3 is a real-time FTIR curve of the mercaptosiloxane polymerization of the embodiment;

[0034] Figure 4 is the JV curve of the battery before and after packaging of the embodiment;

[0035] Figure 5 85° C. after aging for 1000 h. DETAILED DESCRIPTION

[0036] The specific technical solution of the present invention is explained in conjunction with embodiments.

[0037] Embodiment 1

[0038] The preparation method of the fast-curing silicone encapsulant comprises the following specific steps:

[0039] S1. Preparation of vinyl siloxane:

[0040] Cyclosiloxane, vinylsiloxane monomer, hexamethyldisiloxane and concentrated hydrochloric acid were mixed at room temperature, refluxed at 90°C for 5 hours, allowed to stand at room temperature, washed three times with saturated sodium bicarbonate / water / ethanol solution, and distilled at 120°C for 2 hours in a vacuum environment of -0.1Mpa to obtain a colorless transparent oily liquid.

[0041] S2. Preparation of mercaptosiloxane:

[0042] Cyclosiloxane, mercaptosiloxane monomer, hexamethyldisiloxane and concentrated hydrochloric acid were mixed at room temperature, refluxed at 90°C for 5 hours, allowed to stand at room temperature, washed three times with saturated sodium bicarbonate / water / ethanol solution, and distilled at 120°C for 2 hours in a vacuum environment of -0.1Mpa to obtain a colorless transparent oily liquid.

[0043] The packaging process is as follows:

[0044] The vinyl siloxane prepared in step S1, the mercaptosiloxane prepared in step S2 and the photoinitiator are mixed in a mass percentage of 50 parts: 50 parts: 0.5 parts to obtain an uncrosslinked precursor solution; the uncrosslinked precursor solution is spin-coated on a clean glass cover plate at a rate of 3000 rpm for 30 seconds to prepare a siloxane encapsulation adhesive film with uniform thickness; then, the glass cover plate with the siloxane encapsulation adhesive film is covered on the perovskite solar cell, and ultraviolet light is used for initiation, and the ultraviolet light is 365 nm and the intensity is 50 mW / cm 2 The illumination time is 10 to 60 s, so that the double bonds and thiol groups undergo thiol-ene click cross-linking, thereby realizing rapid in-situ lossless encapsulation of perovskite solar cells.

[0045] Embodiment 2-8

[0046] The siloxane encapsulant for perovskite solar cells provided in Example 2-8 is different from that in Example 1 in that the mercapto and vinyl contents of the mercaptosiloxane and vinylsiloxane prepared in steps S1 and S2 are shown in Table 1. The rest is substantially the same as in Example 1 and will not be described in detail here.

[0047] Table 1 Preparation conditions and performance test results of Examples 1-8

[0048]

[0049] As can be seen from Table 1, all embodiments did not cause significant attenuation of the efficiency of perovskite solar cells. It is preliminarily judged that the provided silicone encapsulation glue can achieve lossless encapsulation of perovskite solar cells. In addition, as the content of thiol or double bonds increases, the tensile strength of the siloxane film increases accordingly. On the contrary, the elongation at break shows a decreasing trend. This is mainly because the higher the content of thiol or double bonds on the siloxane molecular chain, the more cross-linking sites, the greater the cross-linking density, the greater the tensile strength of the material, and the material toughness decreases, and the elongation at break decreases. Similarly, in terms of the long-term stability of the battery device, at the same vinyl content, as the thiol content increases, the cross-linking density increases, and the water and oxygen barrier capacity of the encapsulation glue increases accordingly, so that the encapsulated solar cell device shows better long-term stability. Similarly, while maintaining the thiol content unchanged, as the double bond content increases, the cross-linking density of the network increases, and the long-term stability of the encapsulated device is improved.

[0050] Examples 9-12

[0051] The siloxane encapsulant for perovskite solar cells provided in Examples 9-12 is different from that in Example 1 in that the mercapto and vinyl contents of the mercaptosiloxane and vinylsiloxane prepared in steps S1 and S2 are both 0.2 mol / 100 g by determining and adjusting the material ratio, and the ratio of mercapto to double bonds is changed as shown in Table 1. The rest is substantially the same as in Example 1 and will not be described in detail here.

[0052] Table 2 Preparation conditions and performance test results of Examples 9-12

[0053]

[0054] It can be seen from Table 2 that with the increase of the ratio of thiol / double bond, the strength and elongation at break of the siloxane film both show a trend of first increasing and then decreasing. This is because an appropriate excess of thiol can promote the reaction between thiol and double bond, increase the polymerization rate and cross-linking density, and thus affect the change of the mechanical properties of the material. Therefore, the long-term stability of the packaged device is also increased or decreased.

[0055] Example Control Group

[0056] The control group consisted of unencapsulated perovskite solar cells stored in nitrogen.

[0057] The present invention uses a synthetic siloxane encapsulation adhesive to achieve rapid and lossless encapsulation of perovskite solar cells at room temperature, such as Figure 1 shown.

[0058] Figure 2 PSH is mercaptosiloxane, Vin is vinylsiloxane, and PVS is a polymerization product. -1is the stretching vibration absorption peak of the double bond, 2560cm -1 is the stretching vibration absorption peak of -SH, and both disappear after polymerization, indicating that the thiol-ene click reaction has occurred.

[0059] Figure 3 The real-time process of the reaction between the thiol group and the double bond is shown in 1639cm -1 The characteristic peaks attributable to the double bonds gradually disappeared as the reaction proceeded, and the characteristic peaks of -C=O connected to the double bonds of acrylate shifted to higher wavenumbers due to the disappearance of conjugation. The results showed that the cross-linking reaction was completed within 20 seconds.

[0060] like Figure 4 As shown, there is no obvious attenuation in battery efficiency before and after packaging.

[0061] from Figure 5 It can be seen that after aging at 85°C for 1000h, there is no obvious degradation of the perovskite film.

[0062] Through application research, it was found that the efficiency loss of the encapsulated perovskite cell was ≤0.5%; in addition, the encapsulated device maintained 94% to 97% of the initial efficiency after being stored at 85°C and 85% humidity for 1000 hours, while the efficiency loss of the conventional encapsulation process was 3% to 5%, and the encapsulated device was only 80% to 90% of the initial efficiency after being stored at 85°C and 85% humidity for 1000 hours. This process has excellent commercial prospects and will help further promote the industrial application of perovskite photovoltaic devices.

Claims

1. A fast curing silicone encapsulant, characterized in that: According to the mass percentage, including: 10 to 90 parts of vinyl siloxane; 10 to 90 parts of mercaptosiloxane; 0.1~1 part of photoinitiator; The double bond content of the vinyl siloxane is 0.01-0.5 mol / 100 g; the mercapto content of the mercapto siloxane is 0.01-0.4 mol / 100 g; The molar ratio of the mercapto group of the mercaptosiloxane to the vinyl group of the vinylsiloxane is: 1:1, 1:4, 1:2, 2:1 or 4:1; Preparation of Vinyl Siloxane: Cyclosiloxane, vinylsiloxane monomer, hexamethyldisiloxane and concentrated hydrochloric acid were mixed at room temperature, refluxed at 30-120°C for 0.5-5h, allowed to stand at room temperature, washed three times with saturated sodium bicarbonate / water / ethanol solution, and distilled at 120°C for 2h in a vacuum environment of -0.1 Mpa to obtain a colorless transparent oily liquid; Preparation of mercaptosiloxane: Cyclosiloxane, mercaptosiloxane monomer, hexamethyldisiloxane and concentrated hydrochloric acid were mixed at room temperature, refluxed at 30-120°C for 0.5-5h, allowed to stand at room temperature, washed three times with saturated sodium bicarbonate / water / ethanol solution, and distilled at 120°C for 2h in a vacuum environment of -0.1 Mpa to obtain a colorless transparent oily liquid; The cyclosiloxane is one or more of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and tetraphenyltetramethylcyclotetrasiloxane; The vinyl siloxane monomer is one or more of tetravinylcyclotetrasiloxane and methacryloxypropylmethyldimethoxysilane.

2. The use of the fast curing silicone encapsulant according to claim 1, characterized in that: For encapsulation of perovskite solar cells.

3. A method for packaging a perovskite solar cell, characterized in that: The fast-curing siloxane encapsulant of claim 1 is used to rapidly cure under ultraviolet conditions through a photo-induced mercapto-ene click reaction, thereby achieving lossless encapsulation of perovskite solar cells; The photoinitiator is dissolved in vinyl siloxane, and then mixed evenly with mercaptosiloxane monomer, and the uncured polymer siloxane solution is spin-coated on a clean glass cover plate to prepare a siloxane encapsulation adhesive film with uniform thickness; Then, a glass cover with a siloxane encapsulation adhesive film is covered on the perovskite solar cell, and ultraviolet light is used to initiate the thiol-ene click crosslinking of double bonds and thiol groups, thereby realizing rapid in-situ lossless encapsulation of the perovskite solar cell; The spin coating rate is 3000 rpm, the spin coating time is 30 s; the ultraviolet light is 365 nm, and the intensity is 50 mW / cm 2 , the illumination time is 10 ~ 60s.

4. A perovskite solar cell, characterized in that Obtained according to the packaging method according to claim 3.

Citation Information

Patent Citations

  • Ultraviolet light-curing composition

    CN105315675A

  • Filled polydiorganosiloxane-containing compositions, and methods of using same

    CN106164206A

  • Ultraviolet-cured sulfhydryl / alkene organic silicon adhesive and preparation method thereof

    CN107418505A

  • Perovskite solar cell device and packaging method thereof

    CN112701227A